2020
DOI: 10.1136/gutjnl-2019-320368
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting transcriptional heterogeneity in primary gastric adenocarcinoma by single cell RNA sequencing

Abstract: ObjectiveTumour heterogeneity represents a major obstacle to accurate diagnosis and treatment in gastric adenocarcinoma (GA). Here, we report a systematic transcriptional atlas to delineate molecular and cellular heterogeneity in GA using single-cell RNA sequencing (scRNA-seq).DesignWe performed unbiased transcriptome-wide scRNA-seq analysis on 27 677 cells from 9 tumour and 3 non-tumour samples. Analysis results were validated using large-scale histological assays and bulk transcriptomic datasets.ResultsOur i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
200
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(210 citation statements)
references
References 51 publications
10
200
0
Order By: Relevance
“…7 . Our conclusions are supported by a recent single cell RNA sequencing analysis that conclusively shows much higher expression of HLA-DPA1 and HLA-DPB1 mRNAs in malignant epithelial cells isolated from an EBVaGC compared to the EBV-negative GCs they characterized 47 . Single cell RNA sequencing also demonstrated that the EBVaGC malignant epithelial cells exhibited a characteristic enrichment of genes fitting into the gene ontology terms “antigen processing and presentation of peptide antigen via MHC-II” and “interferon-gamma-mediated signaling processes” 47 , precisely mirroring our conclusions based on sequencing of bulk tumor mRNA.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…7 . Our conclusions are supported by a recent single cell RNA sequencing analysis that conclusively shows much higher expression of HLA-DPA1 and HLA-DPB1 mRNAs in malignant epithelial cells isolated from an EBVaGC compared to the EBV-negative GCs they characterized 47 . Single cell RNA sequencing also demonstrated that the EBVaGC malignant epithelial cells exhibited a characteristic enrichment of genes fitting into the gene ontology terms “antigen processing and presentation of peptide antigen via MHC-II” and “interferon-gamma-mediated signaling processes” 47 , precisely mirroring our conclusions based on sequencing of bulk tumor mRNA.…”
Section: Discussionsupporting
confidence: 77%
“…This is supported by immunohistochemical analyses reporting expression of MHC-II molecules, particularly HLA-DR, by most GC epithelial cells 40 , including EBVaGCs 41 , 42 . A very recent single cell RNA sequencing study reported that malignant epithelial cells from an EBVaGC expressed higher levels of both HLA-DPA1 and HLA-DPB1 compared to the other GCs studied, definitively showing that these mRNAs originate from carcinoma cells, rather than professional APCs within the tumor 47 .
Figure 1 Expression of the DP MHC-II α- and β-chain genes in GC subtypes and normal gastric tissue.
…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we evaluated the two distinct single-cell-based platforms, scRNA-seq and CyTOF, for single-cell level immune profiling using surgery-/biopsy-resected tumors and PBMC from gastric cancer patients. The number of previous studies focusing on gastric cancer biopsy in single-cell level is limited [31][32][33] . Our study revealed that the scRNA-seq analysis could cover a broader range of immune cells of TME in the endoscopically-resected small biopsy tumor samples, detecting even small subgroups of B cells or Treg cells in the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if the biopsy samples could be collected before and after the drug treatment in the same patients, the single-cell analysis with these pre-/ post-treatment specimens should provide a great advantage for a deep understanding of the mechanisms of actions and/or biomarker development for cancer therapeutic drugs [41][42][43] . In fact, the single-cell analyses in the biopsy samples, including the scRNA-seq analysis in gastric cancer, have received a lot of attention in recent years, while the number of reports is extremely limited [31][32][33] . Although several technical challenges still need to be cleared for scRNA-seq of the biopsy-resected tumors, especially the cell isolation steps to miss certain cell populations by "bottle-neck effects" 33,44 , this research platform of scRNA-seq should have potential to open the doors to the new generation of cancer biology, overcoming a number of difficulties that currently-used conventional methodologies are facing.…”
Section: Discussionmentioning
confidence: 99%